Dynamic modeling of dual fluidized bed steam gasification for control design. (15th February 2023) - Stanger, Lukas; Schirrer, Alexander; Benedikt, Florian; Bartik, Alexander; Jankovic, Stefan; Müller, Stefan; Kozek, Martin
Abstract: Dual fluidized bed steam gasification allows the production of high-value product gas from woody biomass or biogenic residuals. Advanced control concepts such as model predictive control are promising approaches to improve the process performance and efficiency. These control techniques require dynamic models of the process that can predict the plant's behavior as a function of the manipulated variables. This paper presents a gray-box modeling approach based on mass and energy balances to obtain a mathematical description of the temperatures inside the two reactors and the total mass flows leaving the reactors. The model incorporates data-driven components where first-principle modeling is hardly possible with reasonable effort. An artificial neural network is utilized to model the bed material circulation between the two reactors. Experiments were carried out at a 100 kW pilot plant to generate measurement data both for system identification and model validation. Simulations verify that the model achieves reliable predictions for the dual fluidized bed gasification process. Graphical abstract: Highlights: A gray-box modeling method for dual fluidized bed steam gasification is presented. A dynamic prediction model for control design is provided. Data from a 100 kW pilot plant is used for parameter estimation and validation.